MEDIA PENGENALAN BUDIDAYA TANAMAN CABE BERBASIS MULTIMEDIA - Ezrifal Sany; Sigif Desrian (JURNAL AKADEMIKA)
Dinas Pertanian Dan Tanaman Pangan Kabupaten Kerinci located in Kabupaten Kerinci Provinsi Jambi which at the moment is in need of quality improvement and the ability to manage more to educate the public kabupaten kerinci in order to improve the quality of the agricultural world. Limited time to educate the public kabupaten kerinci, become an obstacle very large calculations for Dinas Pertanian Dan Tanaman Pangan delivery of material that only uses the lecture method as well as the lack of motivation of people in the cultivation process can impede progress and improvement to public kerinci and also to Dinas Pertanian Dan Tanaman Pangan Kabupaten Kerinci in improving the Natural Resources and Human Resources. Making Media Introduction chilli cultivation aims to convey the material in chilli cultivation and increase the community's understanding of the processes in chilli cultivation. Media recognition chilli cultivation consists of user interface for this application. Input to the user interface consists of the familiar chili, pests and diseases, the criteria for winning chili, preparatory cultivation, planting, maintenance, and also harvest and post-harvest. As for the media output generating information based on a selected menu. This application uses the multimedia applications as Adobe flash cs3 main program. The expected result of the application of Media Introduction Cultivation of this chili is the growing interest for the public to chilli crop cultivation and in order to facilitate the staff of dinas Pertanian Dan Tanaman Pangan in the delivery of this material so that the process of delivering more optimal with a very limited time duration, as well as to improve the quality of the Kerinci community in terms of crop farming particularly. Keywords: Adobe Flash CS3, Grow chili, Media Introduction, Multimedia.